Schitt's Creek Season 2 - Ciccoritti, Jerry; Fox, Paul.; Levy, Eugene, 1946-; O'Hara, Catherine; Murphy, Annie; Robertson, Jennifer; Levy, Daniel, 1983- (Toronto, Ontario CBC Home Entertainment, 2016)
"When rich video store magnate Johnny Rose, his soap star wife Moira and their two kids, son David and socialite daughter Alexis suddenly find themselves broke, they are forced to leave their pampered lives to regroup in Schitt's Creek"--Www.imdb.com. Complete second season.
Disc 1. Finding David -- Family dinner -- Jazzagals -- Estate sale -- Bob's bagels -- Moira vs. town council -- The candidate -- Milk money -- Disc 2. Moira's nudes -- Ladies' night -- The motel guest -- Lawn signs -- Happy anniversary.
DVDs.
Container title.
Originally broadcast on television in 2016.
Includes bonus material.
Eugene Levy and others.
CHV rating: 14A.
Keywords: Rich people -- Drama; Poverty -- Drama; Small cities -- Drama; Families -- Drama; Bankruptcy -- Drama; Actors -- Drama; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Drama; Television comedies